The influence of implant surface roughness on decontamination by antimicrobial photodynamic therapy and chemical agents: A preliminary study in vitro - Balderrama, Isis de Fatima [UNESP] (2021)
Background: The aim of this preliminary study was to analyze the effectiveness of three different protocols of decontamination on five commercial moderate rough implants. Material and methods: The types of implants investigated were: Neoporos Drive CM (CM; Neodent (R)), Drive CM Acqua (ACQ; Neodent (R)), SLActive (SLA; Straumann (R)), Osseotite (OT; Biomet 3i (R)) and Nanotite (NT; Biomet 3i (R)). Implant surface properties (n = 2/type of implant; control groups) were analyzed by scanning electron microscopy (SEM) images to determine surface roughness parameters (SRP) and energy disperse X-ray spectrometry to determine the chemical composition. Implants were then inoculated with Aggregatibacter actinomycetencomitans in vitro (n = 6/type of implant;experimental groups) and the contaminated areas were determined in SEM images (500x magnifications). Decontamination of implants was performed in duplicate by three protocols: antimicrobial photodynamic therapy (aPDT), EDTA associated with citric acid (EDTA + CA) and 0.12 % chlorhexidine (CHX). The remaining contaminated area (rCtA) was determined in SEM images (500x magnifications). All quantitative analysis through SEM images were analyzed in ImageJ (R) software for twodimensional parameters. Results: No significant differences were found in SRP among implants (control group), except for Rv (lowest valley) between SLA vs. OT (p=0.0031; Kruskal Wallis post hoc Dunn). NT implants showed highest contaminated area vs. ACQ implants (68.19 % +/- 8.63 % and 57.32 % +/- 5.38 %, respectively; p = 0.0016, Tukey & rsquo;s test). SRP after decontamination showed statistical difference for Ra (arithmetical mean deviation) for all decontamination groups when compared to control (p < 0.05; ANOVA with post-hoc Tukey & rsquo;s multiple comparisons test), only CM implants showed statistical difference when compared decontamination protocols to control with highest modification of SRP for EDTA + AC group. For decontamination analysis, for applicability of different protocols in the same type of implant, only SLA showed statistical significant difference for aPDT vs. EDTA + CA (p = 0.0114; ANOVA with post-hoc Tukey & rsquo;s multiple comparisons test) with lowest rCTA for aPDT, however for ACQ implants the aPDT showed lowest rCTA with no statistical difference (p > 0.05; ANOVA with post-hoc Tukey & rsquo;s multiple comparisons test). No statistical difference was observed between the decontamination protocols at other implant types. Conclusion: It can be suggested that the chemical-physical characteristics of dental implants can be effected by the process of contamination and decontamination by aPDT and chemical agents.